Performance study on effect of convolutional coding in WCDMA system with different channel condition - Mohd. Fahmi, Azlin (2005)
WCDMA system is meant for high data rate transmission such as implementation of the third generation (3G) mobile system. Any mode of mobile transmission is not free from channel impairment such as noise, interference and fading. These channel impairments caused signal distortion and degradation in signal to noise ratio (SNR). Thus one method to overcome this problem is by introducing channel coding in the mobile transmission system. Convolutional coding with coding rate = 1/2 is a standard determined by the 3GPP committee for the 3G system. In order to visualize the effect of convolutional coding in communication channel, simulation method of the WCDMA system is carried out. Thus computer simulation software, MATLAB has been used to evaluate the performance of convolutional coding in AWGN and Multipath Rayleigh Fading channel. Further analysis and discussion is made based on the results obtained. In general, channel coding has improved bit error rate of WCDMA system. However, as the speed of mobile terminal increases the capability of channel coding also degrades. Thus it is suggested that implementation of interleaver to improve quality of the system.